2007
DOI: 10.1111/j.1439-0418.2007.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Host plant effects on the functional response ofNeoseiulus cucumeristo onion thrips larvae

Abstract: The performance of herbivores, natural enemies and their interactions may be affected directly or indirectly by host plant traits, e.g. the physical plant characteristics may influence the search pattern and the functional response of predators. We studied the functional response of adult females of the predatory mite Neoseiulus cucumeris to first instar larvae of Thrips tabaci on three host plants (sweet pepper, eggplant and cucumber). The 24-h leaf disc experiments conducted at 25 ± 1°C, 60 ± 10% relative hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 42 publications
(64 reference statements)
4
34
1
Order By: Relevance
“…Various factors may affect handling time such as predator speed, movement of prey, and the time spent subduing individual prey (Hassell 1978), which could possibly be related to behavioural and physical prey attributes (Ali et al 2011). Madadi et al (2007) and Yao et al (2014) also demonstrated similar results to our study in regards to attack rate and handling time as both studies investigated the functional response of N. cucumeris on Thrips tabaci larvae and first instar of T. flavidulus. Madadi et al (2007) indicated the attack rate for N. cucumeris was 0.048 and the handling time was 1.030 hrs at 25°C.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Various factors may affect handling time such as predator speed, movement of prey, and the time spent subduing individual prey (Hassell 1978), which could possibly be related to behavioural and physical prey attributes (Ali et al 2011). Madadi et al (2007) and Yao et al (2014) also demonstrated similar results to our study in regards to attack rate and handling time as both studies investigated the functional response of N. cucumeris on Thrips tabaci larvae and first instar of T. flavidulus. Madadi et al (2007) indicated the attack rate for N. cucumeris was 0.048 and the handling time was 1.030 hrs at 25°C.…”
Section: Discussionsupporting
confidence: 76%
“…Madadi et al (2007) and Yao et al (2014) also demonstrated similar results to our study in regards to attack rate and handling time as both studies investigated the functional response of N. cucumeris on Thrips tabaci larvae and first instar of T. flavidulus. Madadi et al (2007) indicated the attack rate for N. cucumeris was 0.048 and the handling time was 1.030 hrs at 25°C. Yao et al (2014) indicated the attack rate for N. cucumeris was 0.8856 and the handling time was 0.0298 hrs at 26°C.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The host plant is an interactive component of biological control practices and the characteristics of the host plant need to be considered when determining the predator release rate (Krips et al1999;Loughner et al2008;Madadi et al 2007;Romero & Vasconcellos 2005). Life tables of both predatory mites and spider mites on different plant species provide important information that is needed for the efficient release of predatory mites to control pests in crop fields (Villanueva & Childers 2006;McMurtry et al 2004;Gotoh & Kitashima 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The response of a natural enemy to increasing host density (functional response) is important for the outcome of parasitoidbased biocontrol programs (Berryman, 2004) and together with the numerical response an indispensable element in their biological characterization (Cedola et al, 2001, Gilioli et al, 2005 and an important determinant of their effectiveness as biological control agents (Houck & Strauss, 1985;Jost & Ellner, 2000). Different factors may influence their functional responses, including host plant surface traits (Coll & Ridgway, 1995;Messina & Hanks, 1998;Madadi et al, 2007), host species (Mansfield & Mills, 2004), natural enemy life stages (Seko & Miura, 2008), host age (King, 1994;Ode & Strand, 1995) and spatial complexity (Madadi et al, 2011). However, the functional response of poikilothermic organisms like parasitoids, are greatly affected by temperature (Cave & Gaylor, 1989;Flinn, 1991;Enkegaard, 1994;Bazzocchi & Burgio, 2001;Jones et al, 2003;Kalyebi et al, 2005;Shojaei et al, 2006;Moezipour et al, 2008;Tazerouni et al, 2012).…”
Section: Introductionmentioning
confidence: 99%